Pemberian Edukasi PHBS di SD Negeri 25 Gadut Sawah Dangka dengan Metode PEREKAT - Fradisa, Lisa; Kartika, Kalpana (Universitas Pahlawan Tuanku Tambusai, 2024)
The lack of awareness and knowledge among students regarding Clean and Healthy Living Behavior (PHBS) can significantly impact the quality of school environments and students' overall health. SD Negeri 25 Gadut, Agam Regency, faces similar challenges, including the suboptimal implementation of the School Health Unit (UKS) program and students' low understanding of personal and environmental hygiene. This community service program aimed to enhance students' knowledge and awareness of the importance of PHBS through the PEREKAT method (Religious and Cultural Approach). This method integrates religious values and local culture into health education to build students' character in caring for cleanliness and health. The activities included interactive counseling using PowerPoint and video presentations, demonstrations of the six steps of proper handwashing, and group discussions. Evaluations conducted using pre-tests and post-tests showed significant improvements in students' understanding of PHBS. Moreover, the PEREKAT method successfully engaged students, as indicated by their active participation and numerous questions, particularly regarding the connection between cleanliness and religious values. The results highlight the effectiveness of religious and cultural approaches in health education at the elementary school level. This program is expected to be replicated in other schools to improve students' health and foster cleaner, healthier, and more productive learning environments. Keywords: PHBS, health education, PEREKAT method, cultural approach, healthy living behavior